Labour Demand in Germany: An Assessment of Non-Wage Labour Costs - Yu-Fu Chen; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2003)
The data indicate that non-wage labour costs in Germany have reached a record high in recent years. From 1972 to 2001, the ratio of non-wage labour costs to direct compensation in West German manufacturing industry rose from 55.6 per cent to 81.2 per cent. The topic of non-wage labour costs is increasingly being discussed among and between the political parties because non-wage labour costs are likely to have major negative effects on employment. We follow the real options approach, which allows us to investigate the value to a firm of waiting to adjust labour when the firms revenues are stochastic and adjustment costs are sunk. Simulation exercises show that the interaction between hiring and firing costs, non-wage labour costs and uncertainty can have important ramifications for employment dynamics.
Keywords: 330; real options; labour demand; non-wage labour costs; hiring and firing costs; Germany